Implementation Of Speech Recognition For Voice Command Use - Maturidi, Ade Johar; Osman, Didan; Sulaeman, Muhamad (Ann Publisher, 2025)
Background. Physical limitations of a person sometimes make it impossible to operate a computer with only a keyboard and mouse, Aims. One tool that can be used is a voice command, which is part of speech recognition technology. Methods. The voice signal will be normalized first, and then the coefficient values will be calculated using the Linear Predictive Coding (LPC) and Fast Fourier Transform (FFT) methods. After the coefficient value is obtained, recognition is performed using the backpropagation method of the Artificial Neural Network. Conclusion. The artificial neural network backpropagation method is used because it can adjust its own weights and produce error values that we can determine, thereby improving accuracy. Implementation. This study implements a voice command system using MARF as its speech engine and Java as its programming language.